Guinea School Finance : SABER Country Report 2013 - World Bank Group (World Bank, Washington, DC, 2015)
Systems approach for better education results (SABER) school finance collects, analyzes, synthesizes, and disseminates comprehensive information on school finance policies in primary and secondary education across a range of different education systems. The goal is to enable policymakers to learn about how other countries address the same policy challenges related to school finance and thus how to make well informed policy choices that will lead to improved learning outcomes. SABER school finance is a framework that guides the collection of standardized data to characterize and assess school finance systems around the world. The project primarily examines education finance policies, relying on key informants and official document review to map out the policy landscape. To describe the essential functions of an education finance system, SABER school finance collects information in five data collection areas: (i) school conditions and resources; (ii) allocation mechanisms; (iii) revenue sources; (iv) education spending; and (v) fiscal control and capacity. After identifying how a particular education finance system functions, SABER school finance determines the extent to which the system effectively provides resources so that all children can learn, using six policy goals widely shared across countries: (i) ensuring basic conditions for learning; (ii) monitoring learning conditions and outcomes; (iii) overseeing service delivery; (iv) budgeting with adequate and transparent information; (v) providing more resources to students who need them; and (vi) managing resources efficiently. This country report uses this framework to characterize and assess the education finance system in Guinea.